How can Socratian Methods facilitate e-learning in the Business Environment? - Goule, Eleni; Stamatiadis, Filippos (International Journal of Advanced Corporate Learning (iJAC), 2012)
Information and Communication Technology is changing at an alarming pace creating new forms of learning, such as electronic learning, which seems to be very appealing nowadays across all the business sectors. The purpose of this paper is to discuss how the pillars of Socrates philosophy can be applied in the development of a successful e-learning program within a business environment. Concepts such as language, individual truth, field of expertise, conformity to law and ethics of different infrastructures, personal contact, and intuition will be explored. A case study is undertaken in order to identify whether the proposed parameters can be adopted as relevant and effective to the procedures of e-training within the HR department of a multinational company in Greece. These concepts determine key questions of the methodological approach that need to be answered in order to develop and implement an appropriate and cost-effective e-learning strategy which will help the HR department identify successfully the needs of the employees and create a long-term impact of this state-of-the art educational reality.